Początki zatrudnienia polskich kobiet w NRD (1965-1971) = The beginnings of the employment of Polish women in the German Democratic Republic (1965-1971) - Skobelski, Robert (1968- ) (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The German Democratic Republic since its early beginnings encountered a significant lack of labor force, which made its authorities solicit workers from other socialist countries, especially from the Polish People`s Republic. Since the middle sixties, in accordance with relevant contracts, the German Democratic Republic started to employ Polish workers from border regions, especially women. Until the end of 1971 several thousand Polish women started their jobs in various industrial plants on the other side of the Oder and Neisse.
Keywords: pogranicze polsko-niemieckie; stosunki polsko-niemieckie; Polska Rzeczpospolita Ludowa; Niemiecka Republika Demokratyczna; PRL; NRD; kobiety